065 CXCL13 levels and autoantibody epitope specificities in LGI1-autoantibody syndromes. Issue 12 (14th November 2019) - Michael, Sophia; Ramberger, Melanie; Leite, Isabel Maria; Sen, Arjune; Waters, Patrick; Irani, Sarosh
Abstract : CXCL13 triggers B-cell homing to germinal-centres (GCs). Plasma CXCL13 levels are a marker of GC activity, and CSF CXCL13 levels are elevated in MS, NMDA-R-antibody encephalitis, and NMO. Our objectives were to examine CXCL13 concentrations in LGI1-antibody patients, and the concept of GC-reactions in these patients. Additionally, we explored patient serum binding patterns to two LGI1 domains: LRR and EPTP. End-titrations against full-length LGI1, LRR and EPTP were quantified by live-CBA for 100 sera from 38 LGI1-antibody patients. Serum CXCL13 levels were determined by ELISA in 86 samples from 19 LGI1-antibody patients and HCs (n=20), and evaluated with Mann-Whitney and Spearman's correlation. 98% sera bound both EPTP and LRR, with tight correlation in end-titres (r 0.9257;p<0.0001****) which did not change over disease course. LGI1- antibody patients showed higher serum levels of CXCL13 compared to HCs (p<0.0001). CXCL13 trends over time showed markedly high levels at onset and sharp rises during relapses. LGI1-antibody patients showed high CXCL13 levels with dynamic longitudinal fluctuations. Autoantibodies with reactivity to both EPTP- and LRR-LGI1 domains were detected in equal proportions throughout disease, indicating their ongoing production. Overall, these findings suggest that sustained, ongoing GC-reactions may act as a dominant mechanism of autoantibody production in LGI1-antibody syndromes.